(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article the analysis of subsoil legislation since the independence of our state. In particular, it examined and analyzed legislation of each of the stages of legal reform since the Code, the first law in the sphere of subsoil use is the Code «On Subsoil and mineral raw materials». on May 30, 1992. Of course, in reality, periodically, in practice the law identifies gaps and weaknesses in connection with what the author considered from his own point of view, challenges, achievements, gaps main causes changes in the legislation. Key words: mineral resources, a national company, contract, license, applied law.